Building blockchain apps - Yuan, Michael Juntao (Addison Wesley, 2019)
A Developer's Guide to Blockchain Programming Fundamentals Blockchain development is entering a period of explosive growth, as real applications gain traction throughout multiple industries and cryptocurrencies earn greater acceptance throughout the financial sector. Blockchain represents one of the most promising opportunities for developers to advance and succeed. Building Blockchain Apps is an accessible guide to today's most advanced and robust blockchain programming models and architectures. Building on his pioneering experience, Michael Juntao Yuan covers a wide range of blockchain application development paradigms. The book starts with a concise introduction to blockchain and smart contract technologies. It then guides you through application development on Ethereum-compatible smart contract platforms. Ethereum is the largest and most robust blockchain ecosystem in the world. Coverage includes Ethereum topics such as tools, application frameworks, internal data structures, external data interfaces, and future roadmap An introduction to new blockchain data protocol based on ElasticSearch, which provides insights into the current state of smart contracts and enables new application designs How to build an application-specific smart contract protocol by modifying and customizing the open source Ethereum Virtual Machine and its programming language tools How to extend and support language features that are most suitable for particular kinds of smart contracts (e.g., smart contracts for e-commerce marketplaces) with the open source Lity project How to customize and change the blockchain consensus layer beneath the application layer via the popular Tendermint and Cosmos SDK frameworks A survey of cryptocurrency and financial topics from the developers' point of view, providing an analytical framework for valuating cryptocurrencies and explaining the roles of crypto exchanges Register your book for convenient access to downloads, updates, and/or corrections as they become available. See inside book for details.